2014
DOI: 10.1021/bi5002695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Gain-of-Function LEOPARD Syndrome-Associated SHP2 Mutations

Abstract: The Src homology 2 (SH2) domain-containing protein tyrosine phosphatase 2 (SHP2) is a critical signal transducer downstream of growth factors that promotes the activation of the RAS-ERK1/2 cascade. In its basal state, SHP2 exists in an autoinhibited closed conformation because of an intramolecular interaction between its N-SH2 and protein tyrosine phosphatase (PTP) domains. Binding to pTyr ligands present on growth factor receptors and adaptor proteins with its N-SH2 domain localizes SHP2 to its substrates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 94 publications
6
101
0
Order By: Relevance
“…The answer to this question came from the realization that disease-causing Ptpn11 mutations modify not only the phosphatase activity of SHP2 but also its molecular switch regulatory mechanism that could dictate phenotypic outcome. 167168 …”
Section: Ptp Regulatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The answer to this question came from the realization that disease-causing Ptpn11 mutations modify not only the phosphatase activity of SHP2 but also its molecular switch regulatory mechanism that could dictate phenotypic outcome. 167168 …”
Section: Ptp Regulatory Mechanismsmentioning
confidence: 99%
“…Additional biophysical and computational analyses suggest that in comparison to native SHP2, the LS mutants display a greater tendency to switch from an autoinhibited closed conformation to a catalytically competent open state. 167168 …”
Section: Ptp Regulatory Mechanismsmentioning
confidence: 99%
“…From a biochemical point of view, it has been shown that NScausing mutations induce hyperactivation of the phosphatase (gain-of-function mutation), while NSML-associated mutations result in reduced Shp2 catalytic activity (inactivating mutation) (7,8). How NS-Shp2 and NSML-Shp2 mutants can result in related syndromes while displaying opposite biochemical effects is still a matter of debate (9). Interestingly, a differential impact of these mutants on the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway has been causally linked to the development of hypertrophic cardiomyopathy, which is preferentially found in patients with NSML (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, NS-associated SHP2 mutants that are crippled in their ability to localize via their SH2 domains fail to manifest pathophysiological signaling (18). PTPN11-associated SHP2 mutations exist in an "open" conformation (20,21). Thus, both NS and NSML mutants are endowed with enhanced binding capacity through their SH2 domains to upstream receptor and adaptor proteins, which results in the acquisition of "gain-of-function" properties.…”
Section: Introductionmentioning
confidence: 99%